2004
DOI: 10.1029/2004ja010438
|View full text |Cite
|
Sign up to set email alerts
|

Stormtime subauroral density troughs: Ion‐molecule kinetics effects

Abstract: [1] We report on subauroral plasma density troughs observed by Defense Meteorological Satellite Program (DMSP) satellites during the major magnetic storm of 6 April 2000. The troughs were embedded within strongly irregular, !500-km wide subauroral convection streams, composed of two distinctive parts. The poleward part coincided with strong wave structures, energetic (ring current) ion precipitations, and enhanced vertical ion flows. One or several narrow density decreases were present here. The equatorward pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
75
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(81 citation statements)
references
References 41 publications
6
75
0
Order By: Relevance
“…Trough formation is mainly due to plasma decay in regions of stagnation or chemical and dynamical processes associated with fast plasma motion in the rest frame of the neutral particles (see the review of Rodger et al, 1992, and references therein). Processes like ion outflows (Anderson et al, 1991;Liu et al, 2001) and strong vibrationally excited N 2 (Mishin et al, 2004) may also rise to further deplete the ionosphere under disturbed conditions. Furthermore, Rodger et al (1992) has pointed out that an anti-correlation normally exists between the electron temperature and density in trough regions caused by stagnation or sub-auroral ion drift (SAID).…”
Section: Discussionmentioning
confidence: 99%
“…Trough formation is mainly due to plasma decay in regions of stagnation or chemical and dynamical processes associated with fast plasma motion in the rest frame of the neutral particles (see the review of Rodger et al, 1992, and references therein). Processes like ion outflows (Anderson et al, 1991;Liu et al, 2001) and strong vibrationally excited N 2 (Mishin et al, 2004) may also rise to further deplete the ionosphere under disturbed conditions. Furthermore, Rodger et al (1992) has pointed out that an anti-correlation normally exists between the electron temperature and density in trough regions caused by stagnation or sub-auroral ion drift (SAID).…”
Section: Discussionmentioning
confidence: 99%
“…SAID are considered as a subset of the subauroral polarization streams (SAPS) that include plasma flow events both broad and narrow extents in latitude (Foster and Burke, 2002). Sometimes, SAPS are highly variable and structured (Maynard et al, 1980;Erickson et al, 2002;Mishin et al, 2002Mishin et al, , 2003aMishin et al, , 2004Foster et al, 2004;Mishin and Burke, 2005). Especially strong SAPS-wave structures (SAPSWS), in which V W -oscillations reach AE1-2 km/s and exceed the dc component, follow stormtime substorm onsets.…”
Section: Introductionmentioning
confidence: 99%
“…[9] Mishin et al [2004aMishin et al [ , 2004b have shown that plasma depletion in the ionosphere can occur due to vibrationally excited N 2 in the presence of heated electrons. However, the mechanism is slow and requires minutes at 400 km to 10 or more minutes at 300 km to produce the plasma depletion.…”
Section: Introductionmentioning
confidence: 99%